WHITE STRIPE LEAF4 Encodes a Novel P-Type PPR Protein Required for Chloroplast Biogenesis during Early Leaf Development - Wang, Ying; Ren, Yulong; Zhou, Kunneng; Liu, Linglong; Wang, Jiulin; Xu, Yang; Zhang, Huan; Zhang, Long; Feng, Zhiming; Wang, Liwei; Ma, Weiwei; Wang, Yunlong; et al. (Frontiers in Plant Science, 2017)
Pentatricopeptide repeat (PPR) proteins comprise a large family in higher plants and perform diverse functions in organellar RNA metabolism. Despite the rice genome encodes 477 PRR proteins, the regulatory effects of PRR proteins on chloroplast development remains unknown. In this study, we report the functional characterization of the rice white stripe leaf4 (wsl4) mutant. The wsl4 mutant develops white-striped leaves during early leaf development, characterized by decreased chlorophyll content and malformed chloroplasts. Positional cloning of the WSL4 gene, together with complementation and RNA-interference tests, reveal that it encodes a novel P-family PPR protein with 12 PPR motifs, and is localized to chloroplast nucleoids. Quantitative RT-PCR analyses demonstrate that WSL4 is a low temperature response gene abundantly expressed in young leaves. Further expression analyses show that many nuclear- and plastid-encoded genes in the wsl4 mutant are significantly affected at the RNA and protein levels. Notably, the wsl4 mutant causes defects in the splicing of atpF, ndhA, rpl2, and rps12. Our findings identify WSL4 as a novel P-family PPR protein essential for chloroplast RNA group II intron splicing during early leaf development in rice.